Nuclear EGFR renders cells radio-resistant by binding mRNA species and triggering a metabolic switch to increase lactate production. Issue 3 (September 2015) - Dittmann, Klaus; Mayer, Claus; Paasch, Angela; Huber, Stephan; Fehrenbacher, Birgit; Schaller, Martin; Rodemann, H. Peter
Abstract Background and purpose EGFR is translocated into the cell nucleus in response to irradiation, where it is involved in regulation of radio-sensitivity. The aim of this study is to elucidate the functional role of nuclear EGFR. Material and methods To identify EGFR-bound nuclear proteins and mRNAs, Maldi-TOF analysis and mRNA gene arrays were used. Complex formation of proteins was shown by confocal microscopy, immunoprecipitation and Western blotting. The effect of EGFR binding to mRNAs was exhibited by quantitative RT-PCR. Cellular endpoints were shown by Western blotting, mitochondrial mass quantification, lactate quantification and clonogenic survival assays. Results Maldi-TOF analysis of proteins bound to nuclear EGFR in response to irradiation showed colocalization with Lamin A and heterogeneous nuclear ribonucleoproteins. Confocal microscopy and Western blotting confirmed this colocalization. Both Lamin A and heterogeneous nuclear ribonucleoproteins are involved in mRNA processing. To support a role of nEGFR in this context after irradiation, we isolated EGFR-bound mRNA and observed an EGFR kinase-dependent mRNA stabilizing effect. With the help of DNA microarrays, we identified mRNAs associated with the Warburg effect that were bound to nuclear EGFR. In this context, we observed radiation-induced HIF1α expression, which triggers inhibition of pyruvate dehydrogenase and blocks the tricarboxylic acid cycle. Consequently, we detected mitophagy and increased lactate production, which is associated with increased treatment resistance. Reduction of nEGFR decreased radiation-induced expression of Hif1α and lactate production. Conclusions We showed that nuclear EGFR selectively binds and stabilizes mRNA involved in the Warburg effect in response to irradiation. As a consequence, cells switch from aerobic to anaerobic glucose metabolism, which can be prevented by HIF1α inhibitor BAY87-2243, Dasatinib, Erlotinib or EGFR siRNA.